Neurophysiology of the esophagus. (29th September 2014) - Brock, Christina; Brokjær, Anne; Drewes, Asbjørn Mohr; Farmer, Adam D.; Frøkjær, Jens Brøndum; Gregersen, Hans; Lottrup, Christian
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the methods and characteristics of esophageal afferents in humans; the pitfalls in characterization of mechanosensitive afferents; the sensitization of esophageal afferents in human studies; the brain source modeling in the understanding of the esophagus–brain axis; the use of evoked brain potentials in the esophagus; and measuring descending inhibition in animal and human studies.